Firm on the Male Line, Tentative on the Female: The Surrogate Heir between Article 185 KHI and al-Nawawi's Shāfiʿī Doctrine - Ahmad Fawwaz; Fuat Hasanudin (PFL: Plural Family Law Review, 2026)
The codification of Islamic inheritance in Indonesia has produced a rule with no counterpart in the classical schools, and its standing within the Shafi'i tradition remains unsettled. Article 185 of the Compilation of Islamic Law (Kompilasi Hukum Islam, KHI) allows a grandchild whose parent died before the propositus to take that parent's place. In contrast, the received doctrine, and Imam al-Nawawi in particular, would often exclude the grandchild altogether. This article asks whether the provision is a faithful development of the school or a departure from it, a question earlier scholarship has raised but not resolved. The study reads Article 185 directly against al-Nawawi's treatment of the grandchild in Rawdat al-Talibin and al-Majmu' Sharh al-Muhadhdhab. Using doctrinal-normative legal research, it compares the two frameworks along four declared axes: legal basis, conditions, mechanism, and share size. It tests them on a single gender-specified estate worked through to exact fractions. The Compilation confers an entitlement through a mechanism informed by the obligatory bequest (wasiat wajibah), capped at one third and at the share of an heir of the same degree. At the same time, al-Nawawi admits the grandchild only through the fixed categories of 'asabah and Qur'anic sharer. In the estate tested, the surviving son takes the whole property under al-Nawawi, but two-fifths under the Compilation. Read through the objectives of Shafi'i succession, Article 185 emerges as development rather than deviation, though unevenly: the alignment is firm on the male line and more tentative on the female line, where the daughter's child is reclassified rather than repositioned. The article's contribution is to locate this asymmetry, largely overlooked in the existing literature, and to recast the reform debate as a question of which line the provision can textually secure.